1977
DOI: 10.1104/pp.59.3.478
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins: Metabolism and Biological Activity of N6-(Δ2-Isopentenyl)adenosine and N6-(Δ2-Isopentenyl)adenine in Tobacco Cells and Callus

Abstract: The cytokinin, N6-(A2-isopentenyl)adenine, is found to be at least 3.3 times as active as N6-(A2-isopentenyl)adenosine in promoting the growth of cytokinin-requiring tobacco (Nicotiana tabacum) callus. Absorption rates of N6-(A2-isopentenyl)adenine and N6-(A2-isopentenyl)adenosine by tobacco cells in liquid suspension do not differ significantly. In these cells, N6-(A2-isopentenyl)adenosine-5'-monophosphate, di-, and triphosphate are synthesized in both cases, but 7-glucosylation occurs significantly only with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

1979
1979
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…The relative amount of a specific metabolite formed may differ not only from one plant to another, but also in one particular plant or tissue under different physiological conditions. One of the major metabolites formed from a cytokinin ribonucleoside has been reported to be its corresponding base (9,11,13). In the de novo biosynthesis of cytokinins using a crude enzyme system prepared from plant cells, a cytokinin nucleotide, nucleoside, and base were formed from 5'-AMP and A2-isopentenylpyrophosphate (5).…”
mentioning
confidence: 99%
“…The relative amount of a specific metabolite formed may differ not only from one plant to another, but also in one particular plant or tissue under different physiological conditions. One of the major metabolites formed from a cytokinin ribonucleoside has been reported to be its corresponding base (9,11,13). In the de novo biosynthesis of cytokinins using a crude enzyme system prepared from plant cells, a cytokinin nucleotide, nucleoside, and base were formed from 5'-AMP and A2-isopentenylpyrophosphate (5).…”
mentioning
confidence: 99%
“…In [16,17] i6Ade was converted to the 7-glucosyl derivative in tobacco-cell suspension cultures; it was suggested that cleavage of the isopentenyl side chain was protected by the presence of the glycosidic linkage. The new 9-glucosyl derivative exhibited cytokinin activity in the Amaranths bioassay, although the activity was -1%0 of that of N6-benzyladenine on a molar basis.…”
Section: Resultsmentioning
confidence: 99%
“…It can be readily transported in plant tissue, as shown in [ 181 using synthetic 6-benzylamino-9glucofuranosyl purine. This glucosyl cytokinin can also serve as a storage form which can be activated when needed [ 17,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The cytokinin ribonucleotide can be formed from cytokinin base (3,11,18,20), the ribonucleoside (3,7,17,18) or turnover of cytokinin-containing tRNA (13,22). Alternatively, the ribonucleotide i6Ado-5'-P2 can be synthesized by a de novo pathway from the simple metabolites AMP and A2-isopentenylpyrophosphate (6, 24).…”
Section: Introductionmentioning
confidence: 99%
“…Phenylphosphate and 32-AMP are not substrates for the enzymes. It is proposed that dephosphorylation of cytokinin nucleotide by cytosol 5'-nucleotidases may play an important role in regulating levels of "active cytokinin" in plant cells.The occurrence of cytokinin nrbonucleotide and cytokinin ribonucleoside in plant cells is well documented (2,4,5,10,11).The cytokinin ribonucleotide can be formed from cytokinin base (3,11,18,20), the ribonucleoside (3,7,17,18) or turnover of cytokinin-containing tRNA (13,22). Alternatively, the ribonucleotide i6Ado-5'-P2 can be synthesized by a de novo pathway from the simple metabolites AMP and A2-isopentenylpyrophosphate (6, 24).…”
mentioning
confidence: 99%